Periodontal health status and salivary enzymes level in smokers and non-smokers (comparative, cross sectional study) - Ban Karem; Leka'a M Ibrahim (College of Dentistry/ University of Baghdad, 2014)
Background: Smoking is considering a major risk factor for development and progression of periodontal disease. Investigations regarding the association between smoking and periodontal disease have consistently demonstrated negative periodontal effects and greater probabilities of established periodontal disease among smokers in comparison with non smokers. The purpose of this study was to evaluate the effects of smoking on periodontal health status and on the salivary levels of alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and creatine kinase (CK), and to correlate the clinical parameters of periodontal health with the biochemical findings in smokers and non-smokers. Materials and methods: Unstimulated saliva sample was collected from 25 smokers and 25 non-smokers for biochemical analysis of salivary enzymes. Periodontal parameters including: plaque index, gingival index, bleeding on probing, probing pocket depth and clinical attachment level were recorded. Results: statistical analysis revealed that ALP in saliva was significantly higher in smoker than the non smoker group and there was a highly significant difference in the salivary LDH and CK levels between smokers and non-smokers groups. Plaque index (PLI), probing pocket depth (PPD) and clinical attachment level (CAL) were higher in smokers compared with non smokers, while there was decrease in the number of bleeding sites. Conclusions: smokers group revealed more periodontal tissue destruction than non-smokers group represented by deeper pockets and more clinical attachment level. Salivary enzymes (ALP, LDH and CK) are considered as good biochemical markers of periodontal tissue destruction and can be used to evaluate the effect of smoking on periodontal health status.